Effect of RNA interference on MYB transcripts during flower development in dendrobium orchid / Jennifer Vincent - Vincent, Jennifer (2009)
RNA interference is currently a widely used technique for gene silencing studies in several plant and animal systems. In this study a rapid and inexpensive RNAi technique was used for manipulation of endogenous gene expression in Dendrobium orchids using large quantities of dsRNA which were synthesized in HT115 E. coli. A partial cDNA clone of the MYB9 gene was isolated from Dendrobium Sonia flowers and this was confirmed by sequencing and local alignment analysis using BLAST. The MYB9 gene sequence was cloned into a bacterial expression vector in forward and reverse orientations and transformed into HT115 E. coli strain where induction of bacterial RNA expression was performed by addition of IPTG. RNA produced within the two transformed clones of HT115 E. coli cells was extracted and then annealed to form a crude bacterial extract containing dsRNA. RNA interference studies on orchid buds were carried out by treatment with the crude bacterial extracts mixed with cellite. The effect of the forward, reverse and dsRNA extracts were observed on orchid buds that flowered. Transcripts of the MYB9 gene were successfully reduced in this experiment however this had no visible effect on flower colour. This study has shown that HT115 E. coli can be successfully used to produce large quantities of dsRNA in a short period of time at relatively low cost. The mixture of RNA was able to reduce expression of the target mRNA in Dendrobium flower petals, demonstrating that this might be a useful tool for orchid research and biotechnology.